Homework in Teaching and Learning English as a Foreign Language - Škodová, Magdaléna (Univerzita Pardubice, 2014)
This bachelor thesis deals with homework aimed at developing communicative competence and learner autonomy in English language learning at primary and lower-secondary level. Firstly, the theoretical part focuses on homework throughout the history in comparison to its contemporary function. Then a definition of communicative competence and learner autonomy is presented. The purpose of homework and homework typology are the crucial issue of the theoretical part. Lastly, different attitudes towards homework preparation concerning teachers, pupils and parents are discussed. The practical part is concerned with research study conducted by means of observations and interviews in order to determine frequently assigned types of homework and their influence on developing learner autonomy and communicative competence.
Domácí úkoly ve výuce angličtiny jako cizího jazyka
Keywords: domácí úkoly; funkce domácích úkolů; typy domácích úkolů; komunikační kompetence; autonomie žáka; homeworks; homework purposes; homework types; communicative competence; learner autonomy